Self-Radiopaque Markers Guiding Physician-Modified Fenestration (S-Fenestration) in Aortic Arch Endovascular Repair - Li, Xin; Shu, Chang; Li, Quanming; He, Hao; Li, Ming; Wang, Lunchang; Li, Jiehua; Liu, Dingxiao; Du, Mingyuan (Frontiers in Cardiovascular Medicine, 2021)
Backgrounds and Objectives：TEVAR has currently become the “first-line choice” for descending aortic pathologies. For pathologies locate at aortic arch, TEVAR with PMF (physician modified fenestration) has been gained popularity as an alternative choice. However, stent fenestration is an experience-depend technique and comes with possible adverse events such as mis-alignment. This study aims to introduce the self-radiopaque physician modified fenestration (SF) which uses the radiopaque marker as a guiding indicator. Methods: This is a single center retrospective study of 125 patients who underwent the SF-TEVAR in Second Xiangya hospital from Dec 2015 to Dec 2020. Data includes basic clinical information and technique records of SF-TEVAR with follow-up results. Results：According to the SF-TEVAR protocol, we have performed the procedures on 125 patients and obtained an instant success rate of 98.4%. A total of 140 aortic stent-grafts and 44 bridging stents have been implanted in this study. The operation time is 64.6±19.3 min, X-ray exposure time (from first DSA to last DSA) is 25.6±14.3 min, and contrast volume is 82.2±22.6 ml. The success rate of PMF alignment is 98.4%. One bailout stent-graft was implanted into LSA by chimney technique (0.8%). One fenestration was successfully and immediately corrected after miss-alignment (0.8%). Large simultaneous fenestration was performed in 6 patients (4.8%) for LCCA and LSA, and in 2 patients (1.6%) for IA, LCCA and LSA. 122 out of 125 patients’ LSA have been kept patent by the technique during the follow-up. The bridging stents group consists of 44 patients who received LSA stents while non-bridging stent group includes the other 81 patients. Type Ⅰ endoleak has occurred in 7 patients (5.6%) 1 week after procedure. During follow-up (23±18 month), survival rate is 95.7 % and branch artery patent rate is 97.4%. Conclusions: The SF-TEVAR technique which utilizes the radiopaque marker in stent-graft as an indication for physician modified fenestration in TEVAR seems likely a safe, effective and efficient procedure, which brings acceptable survival rate and branch artery patency rate. SF-TEVAR serves as a progressive alternative method to keep branch artery patent in aortic arch endovascular reconstruction.